Design and Implementation of Parenting Management Training for Bullying Prevention Education at SMKN 8 Merangin - Sofyan, Sofyan; Hendra, Robi; Habibi, Akhmad; Mukminin, Amirul; Pratama, Robin (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
Bullying remains a significant issue in school environments, affecting students’ psychological well-being and social development. This study aims to design and implement a parenting management training program as an educational approach to bullying prevention at SMKN 8 Merangin. Grounded in the recognition of the critical role of parents in shaping children’s behavior, the program was developed as a community-based initiative that integrates parental involvement with school efforts. This study employed a descriptive qualitative design with an implementation-oriented approach to capture both the training process and its conceptual development. The program involved parents and students and was conducted through a blended learning approach, combining face-to-face workshops and online sessions. Training activities included interactive presentations, group discussions, role-playing, and question-and-answer sessions to enhance participant engagement and experiential learning. The results indicate that the program was successfully implemented, with participants actively involved in the learning process and demonstrating increased awareness of bullying and parenting strategies. A key outcome of this study is the development of a conceptual model of parenting management training, which consists of six components: input, training design, implementation strategy, learning process, output, and outcome, supported by participatory learning, technology integration, and school–family collaboration. This model provides a structured and adaptable framework for strengthening parental roles in bullying prevention. The study concludes that parenting management training can serve as a strategic approach to supporting bullying prevention efforts and offers both practical and conceptual contributions for similar educational contexts.